An Evaluation of Fascial Closure Techniques in Open Ventral Hernia Repair: Practice Patterns and Short-Term Outcomes. Issue 11 (November 2019) - Fox, Sarah S.; Huang, Li-Ching; Hooks, W. Borden; Fischer, John P.; Hope, William W.
The best method for fascial closure during hernia repair remains unknown. This study evaluates the impact of fascial closure techniques on short-term outcomes. All patients undergoing open ventral hernia repair were queried using the Americas Hernia Society Quality Collaborative database. Analysis was stratified by suture type (absorbable and permanent) and technique (figure-of-eight, running, and interrupted). Outcome measures included SSI, surgical site occurrence (SSO), SSO requiring intervention, recurrence rate, and quality of life. Descriptive statistics and logistic regression were used. The study included 6544 patients. Two-thirds of surgeons closed fascia during ventral hernia repair with absorbable suture and one-third with permanent suture. In the absorbable group, 17 per cent used figure-of-eight, 46 per cent running, and 4 per cent interrupted suture. In the permanent group, 13 per cent used figure-of-eight, 8 per cent running, and 11 per cent interrupted suture. There was no significant association between SSO and closure technique ( P = 0.2). However, SSO and suture type were significant ( P < 0.001) with the odds of SSO for closure with absorbable suture being 62 per cent higher than the odds of permanent. Fascial closure technique and suture type had no significant association ( P > 0.5) with SSI, SSO requiring intervention, hernia recurrence rate, or HerQLes or NIH PROMIS 3a scores at 30 days or 6 months. Fascial closure technique and suture material do not have a major impact on outcomes in ventral hernia repair. Despite a significantly higher rate of SSO for absorbable sutures than permanent, this did not increase the rate of interventions.